Gender-Related Differences in Patients with Acute Heart Failure: Observation from the Journey Heart Failure—Turkish Population Study - Filiz Akyıldız Akçay; Ümit Yaşar Sinan; Dogaç Çağlar Gürbüz; Özgen Şafak; Hakkı Kaya; Ümit Yüksek; Mehdi Zoghi (Anatolian Journal of Cardiology, 2023)
Background: Gender-related clinical variations in patients with acute heart failure have been described in previous studies. However, there is still a lack of research on gender differences in patients hospitalized for acute heart failure in Türkiye. The aim of this study is to compare the clinical features, in-hospital approaches, and outcomes of male and female patients hospitalized for acute heart failure.